2018
DOI: 10.3390/ma11112256
|View full text |Cite
|
Sign up to set email alerts
|

Morphological, Rheological and Electromagnetic Properties of Nanocarbon/Poly(lactic) Acid for 3D Printing: Solution Blending vs. Melt Mixing

Abstract: The limitation of poor mechanical stability and difficulties in printing electrically conductive components can be overcome owing to the recent introduction of nanotechnology into the field of additive manufacturing (AM) and the consequent development of nonconventional polymer nanocomposites suitable for 3D printing. In the present work, different weight percentages (up to 6 wt % in total) of carbon-based nanostructures—multiwalled carbon nanotubes (MWCNTs), graphene nanoplatelets (GNPs), and a combination of… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
47
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 37 publications
(48 citation statements)
references
References 39 publications
1
47
0
Order By: Relevance
“…The relative viscosity, = increased nonlinearly with increasing filler content, where values for the MWCNT nanocomposites are of 1–2 decades higher compared to the GNPs. At low filler contents, the viscosity function vs. filler content fit well with the adapted Einstein type equation [ 13 , 17 ]: where φ is the filler fraction, [ η ] is the intrinsic viscosity depending on the size, shape, and aspect ratio of the filler, shown in Table 2 . In Figure 2 a the continuous lines present the B-spline curve-fitting of the relative viscosity data at a fixed shear rate ), while the dotted lines show the fitting by the adapted Einstein type linear equation, Equation (2).…”
Section: Resultsmentioning
confidence: 72%
See 2 more Smart Citations
“…The relative viscosity, = increased nonlinearly with increasing filler content, where values for the MWCNT nanocomposites are of 1–2 decades higher compared to the GNPs. At low filler contents, the viscosity function vs. filler content fit well with the adapted Einstein type equation [ 13 , 17 ]: where φ is the filler fraction, [ η ] is the intrinsic viscosity depending on the size, shape, and aspect ratio of the filler, shown in Table 2 . In Figure 2 a the continuous lines present the B-spline curve-fitting of the relative viscosity data at a fixed shear rate ), while the dotted lines show the fitting by the adapted Einstein type linear equation, Equation (2).…”
Section: Resultsmentioning
confidence: 72%
“…The rheological characteristics of the NC-a (with GNP-a, MWCNT-a) reported previously [ 12 , 13 , 14 , 15 ] are compared to those of the NC-b nanocomposites, loaded with GNP-b, MWCNT-b, with varying filler contents of 1.5–9 wt.%, in the PLA matrix polymer. Three essential rheological parameters, which determine the rheology–structure relationship in nanocomposites are identified, as: (i) the degree of dispersion, (ii) the percolation threshold, and (iii) the interfacial interactions.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…The composite samples of 1 mm in thickness and a graphene loading of 8 wt% provide an electromagnetic shielding of 70 dB in the sub-terahertz frequency band with negligible energy reflection to the environment. Composites of the basis of poly(lactic) acid doped with carbon-based nanostructures—multiwalled carbon nanotubes (MWCNTs) and graphene nanoplatelets (GNPs)—with the content up to 6 wt% were produced and studied in terms of the electromagnetic shielding properties by the authors [ 33 ]. It was found that the electromagnetic shielding efficiency (EMI) of nanocomposites strongly depended on the aspect ratio of the nanofillers, whereas the type of processing technique did not have a significant effect.…”
Section: Percolation Behavior Of Polymer-based Composites Doped Wimentioning
confidence: 99%
“…Then, the masterbatches were diluted by extrusion with the neat PLA to produce mono-filler composites of 1.5 and 3 wt% filler contents, as well as bi-filler composites with various proportions of both fillers. Details of sample characterization with the electron microscopy, rheological methods, and dielectric and Raman spectroscopy are presented in [27,28]. The samples and their static conductivities are collected in table 1.…”
Section: Materials and Preparation Techniquementioning
confidence: 99%